Educational Alternatives to the Empowerment Process Village Community - Wisroni Wisroni; Muhamad Fahrur Rozi (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
Education is regarded as the crucial strategy in human power because the mayor attention of educational institute is how to enable the learners as the output to do something based on their own capability. Unfortunately, the education has not had the ability to face this challengeing work. School education, based on its characteristics, is not appropriate for all people from various age. So, it is difficult for a school education to fulfill the expectation of preparing human power maximally, especially to improve countryside people. Developing non-formal educational system may be an right choice for it. The problem is that there are still many non-formal learning activities use the school approach which in turns, will not improve the people. The non-fomal learning activities that can improve people who involve in it, are those which can be applied in all program dimensions, that is having mini and homogenous groups, switching responsibilities, having leadership of learners, "outsiders" as facilitators, and democratization.